Spatial–temporal distribution and evolution of the socialist built heritage in China, 1949–1978 - Xidong Ma; Yukun Zhang; Yan Li; Yujing Li; Feiyang Lin (Heritage Science, 2023)
Abstract As the material product of socialist construction activities, the socialist built heritage (SBH) represents socialist-era achievements and has unique cultural value. However, political controversy and inadequate conservation awareness have produced an unprecedented crisis. The aim of this study was to draw worldwide attention to the value of SBH to promote future conservation. Taking the socialist country of China as a representative example, the spatial distribution and spatial–temporal evolution of SBH during the Socialist Revolution and Construction Period (1949–1978) were explored using GIS analysis tools from typological and holistic perspectives. A geographic detector was also applied to reveal the driving factors that affected the distribution. The results indicate that (1) from both perspectives, the SBH presented uneven and clustering distributions compared with other heritages. High-density areas varied by heritage type but were virtually nonexistent in western and northwestern China. (2) Growth stages existed to different degrees for most types and the holistic SBH, primarily from 1953 to 1965. The centers of military heritage, industrial heritage, transport heritage, and the holistic SBH all exhibited north-to-south migration with narrowing and clustering of range areas. Cities such as Beijing were identified as hotspots. (3) GDP, financial revenue and capital investment constituted the major positive driving factors for the SBH distribution and interacted with other factors, with average altitude ∩ GDP having the strongest interpretation. These findings reveal the spatial–temporal distribution characteristics of Chinese SBH and provide concrete guidance and positive foundations for future conservation in China and the world.